Global SMEs' Strategy - Valerij Dermol; Mitja I. Tavčar (International School for Social and Business Studies, 2012)
In developed countries the number of SMEs vastly exceeds the number ofMNCs. An important share of SMEs are somehow linked to MNCs - but theimpression prevails, that SMEs are in a subordinate position and certainly donot have a global strategy. We argue, however, that there should be partnershiprelations between MNCs and SMEs. The share of importance is conditionedby the degree, how well SMEs understand the MNCs global policy andhow they support it with their activity. Through that MNCs become a part ofSMEs' global strategy, which consequently becomes their strategy as well.The paper includes a number of SMEs' considerations and actions to be includedin the MNCs' global strategy - as well as some propositions uponpublic support needed for this purpose.